SCREENING OF THERMOSTABLE PROTEASE PRODUCING MICROORGANISMS ISOLATED FROM INDONESIAN HOTSPRING - Dewi Seswita Zilda; Eni Harmayani; Jaka Widada; Widya Asmara; Hari Eko Irianto; Gintung Patantis; Yusro Nuri Fawzya (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
Although many proteases had been studied and characterized, only a few of them are commercially available. Protease thermostability is one of the crucial properties for industrialapplication. This research aimed to isolate and to screen the potential isolate which produce thermostable protease. There were 6 isolates (BII-1, BII-2, BII-3, BII-4, BII-6 and LII), isolated using solid Minimal Synthetic Medium (MSM) supplemented with 1.5% skim milk, that have, protease activity. Based on the 16S-rRNA gene sequencing analysis, isolates BII-1, BII-2 and BII- 6 were identified as Bacillus licheniformis, isolates BII-3 and BII-4 were identified as Bacillus subtilis, while isolate LII was identified as Brevibacillus thermoruber. Three isolates (BII-6, BII-4 and LII) were then further investigated for the second screening step using liquid MSM supplemented with 1% skim milk. The isolates (BII-6, BII-4 and LII) optimally produced protease when they were cultivated at 35, 30 and 50o C respectively after 22 h of incubation. Protease produced by BII-6, BII-4 and LII had optimum temperature of 65, 60 and 85o C, optimum pH at 7-8, 8 and 9 and stable up to 100 min at 55, 60 and 75o C respectively.